PENERAPAN APLIKASI LE-DIABET SEBAGAI UPAYA PENINGKATAN PENGETAHUAN DAN KEPATUHAN TERAPI PENDERITA DIABETES MELLITUS - Erlina, Lina; Kamsatun, Kamsatun; Kusnandar, Kuslan; Iriana, Pramita (Poltekkes Kemenkes Bandung, 2025)
Diabetes mellitus (DM) is one of the most prevalent non-communicable diseases globally, with its incidence continuously increasing in Indonesia. Effective DM management requires not only medical therapy but also adequate patient knowledge and adherence to self-care practices. The use of digital technology offers innovative opportunities to support patient education and monitoring. This community service activity aimed to improve the knowledge and therapeutic adherence of patients with diabetes mellitus through the implementation of an Android-based application called Le-Diabet in the working area of Puskesmas Garuda. An interactive technology-based education approach was applied involving 30 DM patients and 14 health cadres. The Le-Diabet application was used for four week to provide information on diabetes management, medication reminders, and blood glucose tracking. Evaluation was conducted using pre-test and post-test questionnaires assessing knowledge and therapy adherence. There was a significant improvement in patients’ mean knowledge scores from 63.9 to 68.2 (p=0.007) and therapy adherence scores from 5.7 to 7.2 (p=0.000). The mean fasting blood glucose level decreased from 167.03 mg/dL to 160.37 mg/dL after the intervention. Although the increase in health cadres’ knowledge was not statistically significant (p=0.481), they showed higher engagement in digital-based education. The implementation of the Le-Diabet application effectively improved patients’ knowledge and adherence to diabetes therapy and showed potential as a digital educational tool for health cadres. It is recommended that the application be integrated into continuous patient education programs at public health centers and further developed with monitoring and automatic reminder features.